ANALISIS UJI KUAT TEKAN BATAKO DENGAN CAMPURAN DEDAK PADI - Ali Yudhiansyah; Ishak Ishak; Deddy Kurniawan (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2022)
Brick is one of the building materials in the form of rock whose hardening is not burned and in the form of a mixture of sand, cement, water, and in its manufacture can be added with other materials (additive). Printed in such a way as to meet the requirements that can be used as material for wall cladding. One alternative that will be used to overcome the above problems is to make bricks with rice bran added material. By utilizing agricultural waste in the form of rice bran, it is expected to reduce environmental pollution and reduce damage to agricultural land. then the formulation of the problem can be taken, namely how is the effect of the compressive strength of brick with the addition of rice bran. knowing the strength of ordinary bricks with bricks that have been mixed with additive materials in the form of rice bran with a composition of 0%, 5%, 10%, 15%. In this study the author uses the experimental method which is a type of quantitative research. This study is intended to examine the effect of a treatment on the object of research. In this study, the test object was made by adding rice bran as a mixture of brick mortar. Then the compressive strength of the bricks was tested at the age of 28 days which made it possible for the bricks to have reached the maximum compressive strength value. From the results of the brick testing, it can be concluded that the composition of rice bran as much as 5% is the most idealmixture because the average compressive strength reaches 112.38 Kg/cm2. with the addition of 10% rice bran, the average compressive strength was 75.55 Kg/ cm2, compared to normal brick which was only 62.33 Kg/ cm2, but after the addition of 15% rice bran the compressive strength decreased to 28.33 Kg/ cm2. With the addition of rice bran to the composition of the concrete block mixture, the average weight of the specimens decreased, because the cavities in the bricks were filled with fine grained rice bran. This shows a high value in the composition of 5% to 10%, because it meets the quality requirements for compressive strength in terms of the established standards, namely SNI 3-0349-1989. The values obtained meet the quality level categories I and II, namely > 100 Kg/ cm2and 70 Kg/ cm2based on the SNI 3-0349-1989 standard.Keywords: Brick, Rice Bran, Compressive Strength.